Sex Estimation SEX ESTIMATION BASED ON MAXILLARY SINUS DIMENSION MEASUREMENTS USING COMPUTED TOMOGRAPHY (CT) SCAN OF PARANASAL SINUS - Hunafa, Alya Hasna (Jurnal Forensik dan Medikolegal Indonesia, 2025)
Sex estimation is a very important step in forensic identification. Personal identification will be accurate if 100% of the entire skeleton is obtain, but it cannot be done in several cases such as severe violence and mass disasters. Therefore, an identification parameters that are not easily damaged and are often intact is required, such as the maxillary sinus, which through this study aims is to determine the difference in volume of the maxillary sinus in male and female. This study is an observational study with cross sectional design used a total of 33 samples of Paranasal sinus from 17 men and 16 female in the radiology department of Sultan Agung Islamic Hospital Semarang for the period January – December 2024 who met the inclusion and exclusion criteria. The analysis showed that there are significant difference in there was a significant difference in the volume of the maxillary sinus in men and female, with a value of p = 0.003, with the average volume of the maxillary sinus in men being 20.67 cm3 and the dimension of the volume of the maxillary sinus in female being 16.7 cm3. Based on these results, it was concluded that there was a significant difference between male and female maxillary sinuses.